Learning science outside the classroom: development and validation of the out-of-school learning environments perception scale - Şen, Ahmet İlhan; Kılıç, Hülya Ertaş; Oktay, Özlem; Ekinci, Serkan; Kadırhan, Zafer (SPRINGER, 2021)
The purpose of this study was to develop and validate a novel scale, the Development and Validation of Out-of-School Learning Environments Perception Scale (OSLEPS), that measures middle school students’ perceptions of out-of-school learning environments. A total of 990 middle school students (583 females and 407 males) participated in the study. Exploratory factor analysis was conducted using the data collected from 549 students to provide evidence for the validity and reliability of the structure of the OSLEPS and its underlying subscales. A four-factor structure emerged: incentive for learning, learning benefits, integration, and involvement. Then, confirmatory factor analysis was conducted using the data collected from 441 students to confirm the four-factor structure of the 16-item OSLEPS. Further validation of the OSLEPS was performed based on the students’ gender and grade levels. Statistical analyses indicated that the OSLEPS is a valid instrument that can be used to investigate middle school students’ perceptions of out-of-school learning environments and viewed as an alternative to existing scales in the related area. Further internal and external validity with additional samples and other out-of-school learning settings is warranted.
Keywords: Middle school students; Out-of-school learning environments; Perception; Scale development